2011
DOI: 10.1007/s00122-010-1523-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel quantitative trait locus for Fusarium head blight resistance in chromosome 7A of wheat

Abstract: A Chinese Spring-Sumai 3 chromosome 7A disomic substitution line (CS-Sumai 3-7ADSL) was reported to have a high level of Fusarium head blight (FHB) resistance for symptom spread within a spike (Type II) and low deoxynivalenol accumulation in infected kernels (Type III), but a quantitative trait locus (QTL) on chromosome 7A has never been identified from this source. To characterize QTL on chromosome 7A, we developed 191 7A chromosome recombinant inbred lines (7ACRIL) from a cross between Chinese Spring and CS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 43 publications
2
17
1
Order By: Relevance
“…Xbarc121. This result suggests that the 7AL QTL may be the same QTL as previously 21 reported in these various lines. …”
supporting
confidence: 87%
“…Xbarc121. This result suggests that the 7AL QTL may be the same QTL as previously 21 reported in these various lines. …”
supporting
confidence: 87%
“…In 2011, Jayatilake et al reported a QTL from CS-Sumai 3-7ADSL with a high level of FHB resistance for symptom spread within a spike (type 2) and low deoxynivalenol accumulation in infected kernels (type 3). Designated as Fhb7AC, this QTL mapped near the centromere of the chromosome 7A and explained a similar level of resistance than the QTL detected in this study on chromosome 7A (22% phenotypic variation for type 2 and 24% for type 3 resistance, Jayatilake et al 2011). Further testing will be necessary to uncover whether or not those two QTLs are identical or at proximity.…”
Section: Genetic Architecture Of Fhb Resistance In Triticalementioning
confidence: 65%
“…Therefore during the last decade a number of quantitative trait loci (QTL) mapping studies using molecular markers were conducted. The first mapped QTL originated from the Chinese spring wheat accession ‘Sumai 3’ or its derivatives [1][3]] and later efforts were undertaken to integrate these QTL into adapted germplasm [4][6]. This was followed by the identification and mapping of QTL for Fusarium resistance and mycotoxin accumulation in a number of bi-parental winter wheat populations [7][13], as well as efforts to introduce the novel QTL into elite background [14].…”
Section: Introductionmentioning
confidence: 99%